1989
DOI: 10.1111/j.1471-0528.1989.tb03281.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing neonatal morbidity in gestational diabetic pregnancy

Abstract: Summary. The influence of obstetric factors and indices of maternal blood glucose control on neonatal morbidity was examined in 261 women with gestational diabetes. A reference group of 218 women, matched for age and day of delivery, within 1 week, was used for comparison. Perinatal morbidity was significantly more frequent in the gestational diabetic pregnancies (23%) than in the reference group (13%), whereas the occurrence of large‐for‐gestational‐age infants was not different between the groups. Infants b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…It may be that blood glucose level is a marker of a metabolic state associated with higher risk, rather than the direct cause of complications. Similar results have been observed by some authors who have found that after adjusting for maternal age, parity, and maternal body weight there was no correlation between blood glucose level and neonatal birth weight [3,15,16] . A Naylor et al study reported that cesarean sections were more common in patients diagnosed as having GDM and it was seen in those with no macrosomia [17] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It may be that blood glucose level is a marker of a metabolic state associated with higher risk, rather than the direct cause of complications. Similar results have been observed by some authors who have found that after adjusting for maternal age, parity, and maternal body weight there was no correlation between blood glucose level and neonatal birth weight [3,15,16] . A Naylor et al study reported that cesarean sections were more common in patients diagnosed as having GDM and it was seen in those with no macrosomia [17] .…”
Section: Discussionsupporting
confidence: 90%
“…Perinatal mortality among the infants of mothers with gestational diabetes mellitus has been reduced to the rate that is not totally different than that of the general non-diabetic population [1][2][3] . Improved perinatal care has prevented such increase in perinatal mortality.…”
Section: Introductionmentioning
confidence: 96%
“…4 Infact, a high prevalence of gestational diabetes around 18% has been reported in India. 5 GDM has been recognized as a clinical entity for 50years. 6 Gestational Diabetes Mellitus (GDM) is defined as carbohydrate intolerance with recognition in or onset during pregnancy irrespective of the treatment with diet or insulin.…”
Section: Discussionmentioning
confidence: 99%
“…İlk kez gebelikte ortaya çıkan herhangi bir düzeydeki glukoz intoleransı olarak tanımlanan GDM, gebe sağlığı ve hasta gebeden dünyaya gelecek bebeklerin sağlığını olumsuz etkileyen bir problemdir. Annede hipertansif problemlere, doğum eylemi problemlerine, gebelik sonrasındaki hayatta yüksek Diabetes Mellitus gelişme riskine yol açan, hasta anne bebeğinde perinatal mortaliye ve morbiditeyi arttıran GDM'un, tüm gebeliklerin % 7-36'sı gibi önemli bir kısmını etkilediği bulunmuştur (5,6,7). Gestasyonel diyabet tarama ve tanısı ACOG (American Collage of Obstetrics and Gynecology ) ve ADA (American Diabetes Association)'nın tarama programına göre rutin olarak 24-28 haftalık gebelere önceden diyabet tanısı almamışsa 75 mg OGTT yapılıp açlık, 1. saat ve 2. saat glikoz ölçümü yapılır.…”
Section: Introductionunclassified